2024
DOI: 10.7554/elife.87726
|View full text |Cite
|
Sign up to set email alerts
|

A novel computational pipeline for var gene expression augments the discovery of changes in the Plasmodium falciparum transcriptome during transition from in vivo to short-term in vitro culture

Abstract: The pathogenesis of severe Plasmodium falciparum malaria involves cytoadhesive microvascular sequestration of infected erythrocytes, mediated by P. falciparum erythrocyte membrane protein 1 (PfEMP1). PfEMP1 variants are encoded by the highly polymorphic family of var genes, the sequences of which are largely unknown in clinical samples. Previously, we published new approaches for var gene profiling and classification of predicted binding phenotypes in clinical P. falciparum isolates (Wichers et al., 2021), whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 95 publications
(228 reference statements)
0
1
0
Order By: Relevance
“…While laboratory strains are essential for studying Plasmodium biology, they are not necessarily representative of circulating parasite populations. Genome-wide transcriptomic studies have demonstrated inherent differences in gene expression between culture-adapted strains and natural infections (23)(24)(25)(26). Moreover, natural infections are often complex with individuals frequently carrying multiple clones (27)(28)(29)(30)(31).…”
Section: Introductionmentioning
confidence: 99%
“…While laboratory strains are essential for studying Plasmodium biology, they are not necessarily representative of circulating parasite populations. Genome-wide transcriptomic studies have demonstrated inherent differences in gene expression between culture-adapted strains and natural infections (23)(24)(25)(26). Moreover, natural infections are often complex with individuals frequently carrying multiple clones (27)(28)(29)(30)(31).…”
Section: Introductionmentioning
confidence: 99%